2011
DOI: 10.1590/s1679-62252011000300014
|View full text |Cite
|
Sign up to set email alerts
|

Passage of fish larvae and eggs through the Funil, Itutinga and Camargos Reservoirs on the upper Rio Grande (Minas Gerais, Brazil)

Abstract: The objective of this study was to evaluate the passage of fish eggs and larvae through the Funil, Itutinga and Camargos Reservoirs, located in the upper Rio Grande basin, Minas Gerais, Brazil. Samples were taken downstream and upstream of the dams using a conical ichthyoplankton net and were collected every two weeks, twice per sampling day, between November 2008 and March 2009. Although eggs and larvae were abundant immediately upstream of the reservoirs, no ichthyoplankton were captured immediately downstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 12 publications
(19 reference statements)
1
32
0
Order By: Relevance
“…At Lajeado Dam, fish migrating downstream were virtually absent from the ladder (Agostinho et al, 2011), and the abundance of eggs and larvae declined dramatically along the reservoir (Agostinho et al, 2007b). The similar trends observed at Peixe Angical and Lajeado, together with other evaluations (Agostinho et al, 2007b;Lopes et al, 2007;Suzuki et al, 2011), indicate that large Neotropical dams may fail to allow the downstream passage of young and adults.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…At Lajeado Dam, fish migrating downstream were virtually absent from the ladder (Agostinho et al, 2011), and the abundance of eggs and larvae declined dramatically along the reservoir (Agostinho et al, 2007b). The similar trends observed at Peixe Angical and Lajeado, together with other evaluations (Agostinho et al, 2007b;Lopes et al, 2007;Suzuki et al, 2011), indicate that large Neotropical dams may fail to allow the downstream passage of young and adults.…”
Section: Discussionmentioning
confidence: 66%
“…For example, young (larvae and eggs) do not drift toward downstream areas, probably because they sink in the reservoir (Agostinho et al, 2007b;Suzuki et al, 2011). In addition, the only study that rigorously evaluated the downstream passage of adult fish (Agostinho et al, 2011) revealed that downstream movements through the ladder at Lajeado Dam, Tocantins River, are virtually absent despite the large number of ascending fish recorded over the year.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study add the presence of initial developmental sites (floodplain lakes) in the lotic stretches upstream of the reservoir, primarily in the tributaries (Mortes and Capivari). Although the presence of the fish lift is important for maintaining connectivity between habitats, the functioning of this fish passage should be studied and carefully monitored because there is no descending ichthyoplankton migration downstream (Suzuki et al, 2011). The absence of this migration makes the Funil fish lift one way, which could compromise fish species recruitment downstream of the dam (Suzuki et al, 2011) and consequently undermine its value in conserving the basin's fish species .…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of the fish lift is important for maintaining connectivity between habitats, the functioning of this fish passage should be studied and carefully monitored because there is no descending ichthyoplankton migration downstream (Suzuki et al, 2011). The absence of this migration makes the Funil fish lift one way, which could compromise fish species recruitment downstream of the dam (Suzuki et al, 2011) and consequently undermine its value in conserving the basin's fish species . Its function should be primarily aimed at maintaining genetic flow between populations, where in principle, the populations upstream and downstream would be self-sustaining due to the occurrence of spawning and nurseries areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation